Potential Tax Reforms аnd Kuwait Economic Growth - K. Lawler; F. Ali Al-Sayegh (Вісник Київського національного університету імені Тараса Шевченка. Серія Економіка)
The objective of this study is to identify whether tax reforms are viable in Kuwait in order to create more government income from sources other than oil. The study examines the relationship between the changes in tax revenues, changes in oil revenue and changes in GDP in Kuwait using time series data from 1998 to 2015. The Augmented Dickey-Fuller (ADF) is used to check for the existence of a unit root. The cointegration test is applied to test for long term relationships between variables using the General Least Square (GLS) method of estimation. The results of the tests find that the impact of changes in tax revenues on changes in the GDP of Kuwait is insignificant. Therefore, Kuwait's government could rationally implement tax reforms to have incremental sources of income other than oil revenue. Moreover, it is argued that the government might consider implementing broad based consumption taxes and value added taxes into the tax structure Kuwait, and to invest the revenues from those taxes in productive policies, to induce long term economic growth.